EARLY POSTOPERATIVE COMPLICATION FOLLOWING FILTRATION SURGERY IN DR. KARIADI GENERAL HOSPITAL SEMARANG 2020-2022: Oral Presentation - Observational Study - Resident - Zulfa, Mazidah; Puspasari, Denti; Maharani,; Rahmi, Fifin L (Ophthalmologica Indonesiana, 2024)
Introduction & ObjectivesFiltration surgery is the most frequent surgery in managing glaucoma. Although trabeculectomy isgenerally a safe and effective procedure, complications can occur. The purpose of the study was todescribe the early postoperative complications in patients who had undergone filtration surgery.MethodsThis study was a retrospective study that uses secondary data from electronic medical records ofpatients who had filtration surgery between January 1, 2020, and December 31, 2022, in KariadiHospital Semarang. Preoperative data include age, gender, visual acuity, intraocular pressure, andtype of glaucoma. The incidence of early postoperative complications was described up to 3 weeks offollow-up.Results287 eyes were obtained from 266 patients who underwent filtration surgery. 168 eyes (58.5%) hadphaco-trabeculectomy, 117 eyes (40.77%) had trabeculectomy and 2 eyes (0.7%) had ECCEtrabeculectomy.Primary angle closure glaucoma (126 eyes, 43.9%) was the most common type ofglaucoma treated with filtration surgery. During the 3-week follow-up period, 93 eyes (32.4%)experienced an early complication with trabeculectomy being more common (17.42%) thancombined surgery. The commonest complication found was hypotony in 69 eyes (24%). Othercomplications include hyphema (3.14%), transient intraocular pressure elevation (3.14%), blebleakage (2.09%), suprachoroidal haemorrhage (0.7%), subhyaloid haemorrhage (0.35%) and retinalhaemorrhage (0.35%).ConclusionThis study found the most common early postoperative complication of filtration surgery washypotony. This complication occurs frequently after trabeculectomy.